(untitled) (Research, Society and Development, 2021)
Crinum americanum L. is a monocotyledonous plant belonging to the Amaryllidaceae family that has economic importance for being ornamental and pharmacological for containg alkaloids that can present anticholinesterase action in its chemical composition. Callus induction is important both for biomass production and for the accumulation of secondary metabolites, especially those of the alkaloid class. In this sense, biotechnological techniques can be used as an alternative to make the process viable. Nowadays, it is known that monocotyledonous plants present great difficulties to be cultivated in vitro, among which the species C. americanum stands out. As a result, the objective this study was to demonstrate the most efficient concentrations of growth regulators 2,4-D and BAP associated with solidifying agents Agar and Phytagel for in vitro cultivation of this species in order to present alternatives to increase production of biomass and help in future studies in the area of ​​somatic embryogenesis and/or for accumulation of secondary metabolites. For the evaluation of cell development, growth in diameter was observed and the callus growth curve was also obtained through sacrificial sampling. It was observed that when the friable callus is inoculated with the correct balance between growth regulators in MS medium supplemented with 3% sucrose (m/v), which contains the solidifying agent Phytagel at 0.2% (m/v), cells tend to grow faster and consequently the gain in biomass is greater.